(untitled) (Research, Society and Development, 2022)
Systemic Arterial Hypertension is a clinical condition, based on the combination of several factors, characterized by a sustained elevation in blood pressure levels ≥ 140 and / or 90 mmHg. Children and adolescents are considered hypertensive when the systolic blood pressure and / or diastolic blood pressure are higher than the 95 mmHg percentile. To investigate the relationship between obesity and systemic arterial hypertension in children and adolescents. For data collection, a search was made in the Virtual Health Library databases through the websites: Latin American and Caribbean Literature in Health Sciences, Scientific Electronic Library Online, Physiotherapy Evidence Database and National Library of Medicine. The search terms “systemic arterial hypertension”, “children”, “adolescents”, “incidence” were used in an associated manner. The criteria used to select the articles were that they addressed the proposed theme, Qualis Periodical from A1 to B3, published from January of 2015 to December of 2020, field studies, available in English, Portuguese and Spanish. Twenty studies of the following types were analyzed: cross-sectional observational, qualitative and quantitative study, in which 8 were chosen because they had information on the subject of the present study. It is concluded that children who have a higher body mass index, tend to have a greater predisposition to systemic arterial hypertension, this factor is associated with changing factors such as poor diet and physical inactivity.